Menghidupkan Kuliner Nusantara - Putri Aulia Soleha; Sasta Nisrina Fatihah; Siti Ayuwidya (Niswantara: Jurnal Pengabdian Kepada Masyarakat, 2024)
Kue bolen, a traditional Indonesian pastry, is made with various ingredients such as pisang, cokelat, and keju. The study focuses on the production process, consumer preferences, and the impact of factors on product quality. The research uses observation, consumer surveys, and organizational analysis to understand consumer preferences and factors affecting product quality. The Business Model Canvas (BMC) is a strategic management tool used to develop and apply a business model systematically. The study identifies the main challenges and benefits of using BMC in technology startups, highlighting its effectiveness in balancing business needs with market needs and optimizing resource use. The SWOT analysis is used to evaluate a company's strengths, weaknesses, opportunities, and threats. The study provides recommendations for improving operational efficiency, investing in research and development, and implementing aggressive business strategies to maximize market potential.